Spectrum of Nasopharyngeal Cancers Seen in the Department of Radiation Oncology University College Hospital, Ibadan - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Nasopharyngeal cancers were initially thought to be an uncommon disease in Nigeria, but recent studies have shown a steady increase in the incidence of the disease with an associated increase in morbidity and mortality due to late presentation.Aims:The aims are to evaluate the mode of presentation and referral pattern of nasopharyngeal cancer patients seen.Settings and Design:This was a retrospective review of patients with nasopharyngeal cancer seen in the department of Radiation Oncology U.C.H. Ibadan from 2000 to 2009.Methods and Material:Patients’ biodata, clinical–pathologic presentation, and site of referral were retrieved using data extraction form and subsequently analyzed using Microsoft Excel (2013).Statistical Analysis Used:It is a descriptive analysis.Results:A total of 205 patients with histologically confirmed nasopharyngeal cancer seen during the study period were analyzed. The mean age of the patients was 41.7 years with 144 (70.2%) males and 61 (29.8%) females. The commonest presenting complaint was cervical lymphadenopathy in 98.5% of patients followed by nasal blockade, nasal discharge, and epistaxis with 82.0%, 78.0%, and 51.2%, respectively. Undifferentiated carcinoma was the commonest histologic type (68.8%). Majority of patients were civil servants (33.2%). The habit of smoking and alcohol ingestion was unspecified in majority of patients (43.4%). Ingestion of smoked fish has been found in majority of patients (122, 59.5%) with the disease in this study. Most of the patients came from southern part of the country which coincides with the geographic distribution of Burkitt’s lymphoma; hence, the possibility of Epstein–Barr virus as one of the likely causative agents. None of the patients presented with stage I disease, while most patients presented at stage III 129 (62.9%).Conclusions:Nasopharyngeal cancer is common. Cervical lymphadenopathy, nasal blockade with undifferentiated histology, and late presentation were the norm. Referrals were from all the regions of the country.